Teacher Ability in Digital Learning for Increasing Early Childhood Creativity - Huwaina Awanis; Sudaryanti; Suci Aulia Sari (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The integration of technology into early childhood education has become a necessity in the Society 5.0 era, particularly to support the development of creativity through interactive and innovative approaches. This study aims to identify the level of kindergarten teachers’ understanding of digital learning as a means to foster creativity in children aged 4 to 6 years. A descriptive quantitative method was employed through a survey of 52 kindergarten teachers in the city of Lhokseumawe. Data were collected using online questionnaires and interviews, and analyzed using percentage-based techniques. The findings indicate that the majority of teachers lack understanding of digital learning (87%), are unfamiliar with the concept of constructive play (79%), and report the absence of digital learning guidebooks (85%). These results highlight an urgent need for comprehensive training in digital pedagogy and the development of technology-based educational play tools to enhance creativity in early childhood learners.